A qualitative study of the factors impacting implementation of the national action plan to contain antimicrobial resistance (2016-2020) in medical institutions - Yun Tao; Ying Wang; Yu Zhang; Yong Han; Jiajia Feng; Hong Cheng; Likai Lin (BMC, 2024)
Abstract Objective Antimicrobial resistance (AMR) has emerged as a serious global public health crisis. In response, 2016, 14 ministries in China, under the leadership of the National Health Commission, collaboratively issued the National Action Plan (NAP) to Contain Antibacterial Resistance (2016-2020). The NAP outlines strategies for medical institutions to adopt stewardship and implement AMR control. The purpose of this study was to comprehend stakeholders' perceptions of the NAP and explore the factors that influence its implementation in medical institutions. Methods Semi-structured interviews were conducted with practitioners from medical institution in March and April 2021. Interviews were audio-recorded, transcribed and analyzed using thematic analysis via the framework approach. Results Twenty practitioners, representing diverse roles (4 administrators, 7 clinicians, 3 microbiologists, 3 pharmacists, 3 nosocomial infection management personnel) from seven institutions, participated in the study. Substantial efforts have been undertaken to regulate the rational use of antibiotics and enhance the management of hospital infections. Participants demonstrated awareness and concern regarding antimicrobial resistance, with widespread support expressed for the NAP. Among all professions, there were varying opinions on whether they felt restricted in their daily work. The tertiary hospitals have established multidisciplinary cooperation mechanisms. Six main themes were identified as both barriers and facilitators to the implementation of the NAP in the medical institutions: individual factors, leadership, multidisciplinary collaboration, patient factors, training and culture. The capacity for administrative attention is constrained or limited, poor enforcement of guidelines, insufficient specialist staff and the liability pressure on clinicians were perceived barriers. To containing AMR in medical institutions, management of hospital infections, the public's knowledge of antibiotics' usage, routine education and multidisciplinary support would be facilitators. Conclusions Practitioners from medical institutions were highly supportive for the NAP. Consideration of practitioners' perceived barriers and facilitators might enhance implementation of the NAP to contain antimicrobial resistance.